2007
DOI: 10.1016/j.bbamcr.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Probing the mechanism of FET3 repression by Izh2p overexpression

Abstract: We previously reported a role for the IZH2 gene product in metal ion metabolism. Subsequently, Izh2p was also identified as a member of the PAQR family of receptors and, more specifically, as the receptor for the plant protein osmotin. In this report, we investigate the effect of Izh2p on iron homeostasis. We show that overproduction of Izh2p prevents the iron-dependent induction of the Fet3p component of the high-affinity iron-uptake system and is deleterious for growth in iron-limited medium. We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(80 citation statements)
references
References 46 publications
2
78
0
Order By: Relevance
“…Hence, we have already demonstrated the efficacy of this system for testing models of signal transduction and identifying novel players in the pathway. We also demonstrated that human PAQRs, when expressed in yeast, repress FET3 in response to activation by their respective agonists (Kupchak et al, 2007;Smith et al, 2008), thus demonstrating that the mechanism of signal transduction may be conserved in the PAQR family.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…Hence, we have already demonstrated the efficacy of this system for testing models of signal transduction and identifying novel players in the pathway. We also demonstrated that human PAQRs, when expressed in yeast, repress FET3 in response to activation by their respective agonists (Kupchak et al, 2007;Smith et al, 2008), thus demonstrating that the mechanism of signal transduction may be conserved in the PAQR family.…”
mentioning
confidence: 68%
“…The ypc1⌬ydc1⌬ double mutant (MAT␣;ade2;his3;leu2;trp1;ura3;can1;ypc1::LEU2;ydc1::TRP1) and the isogenic W303-1A wild type (MAT␣;ade2;his3;leu2;trp1;ura3;can1) background strains were a gift from Dr. Howard Riezman at the University Basel, Switzerland (Schorling et al, 2001). FET3-lacZ was used as a FET3 promoter/lacZ reporter plasmid and was described previously (Kupchak et al, 2007). IZH2 and YPC1 were cloned into pRS316-GAL1 via gap repair as described previously (Lyons et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…meiotic arrest. mPRs and AdipoQ receptors can functionally couple to the same signal transduction pathway in yeast, suggesting a common mechanism of action (Kupchak et al, 2007). Adiponectin receptors signal through multiple pathways, including the adaptor protein APPL1, which links to the trafficking GTPase Rab5 (Buechler et al, 2010;Mao et al, 2006) or p38 MAPK (MAPK14) (Heiker et al, 2010).…”
Section: Discussionmentioning
confidence: 99%